Synthetic Phage for Tissue Regeneration - So Young Yoo; Anna Merzlyak; Seung-Wuk Lee (Mediators of Inflammation)
Controlling structural organization and signaling motif display is of great importance to design the functional tissue regenerating materials. Synthetic phage, genetically engineered M13 bacteriophage has been recently introduced as novel tissue regeneration materials to display a high density of cell-signaling peptides on their major coat proteins for tissue regeneration purposes. Structural advantages of their long-rod shape and monodispersity can be taken together to construct nanofibrous scaffolds which support cell proliferation and differentiation as well as direct orientation of their growth in two or three dimensions. This review demonstrated how functional synthetic phage is designed and subsequently utilized for tissue regeneration that offers potential cell therapy.